Tourism experiences as the remedy to nostalgia: conceptualizing the nostalgia and tourism nexus - Christou, Prokopis A. (My University, 2020)
Heimweh, for centuries, designated a medical condition; Humans have pursued travelling and seeking experiences that would ease symptoms of nostos’s algos (pain caused due to return cravings). In current days, nostalgia’s constructive effects are acknowledged. Yet inconclusive findings of the construct, call for a consolidation of theory that has in so far relied on case studies and confirmations of its beneficial effects. Through a systematic review, this paper examines how tourism may comfort people who are left with the longing for the bygone dissatisfied. A holistic conceptualization of the complex system of nostalgia and tourism interplay is presented while guiding future research.
Keywords: Emotions; Experience; Nostalgia; Tourism; Tourist